2011
DOI: 10.4028/www.scientific.net/amr.189-193.3726
|View full text |Cite
|
Sign up to set email alerts
|

Research on Defects of Titanium Alloy Laser Rapid Forming

Abstract: In the process of metal powder laser rapid forming, various defects may be caused in forming parts on account of technical parameters, equipment performance, material characteristics and other factors. While dimensional accuracy error and surface sticky powder caused by powder factor are the two major defects of forming parts. The experimental analysis finds that less or over accumulation resulting from powder feed delay is the main reason for affecting the dimensional accuracy of cladding and the main reason … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Shang et al [10] researched the various defects which may be caused in forming parts on account of technical parameters, equipment performance, material characteristics, and other factors in the process of metal powder laser rapid forming. The results show that less or over accumulation resulting from powder feed delay is the main reason for affecting the dimensional accuracy of cladding and the main reason which affects the appearance of surface sticky powder is specific energy.…”
Section: Introductionmentioning
confidence: 99%
“…Shang et al [10] researched the various defects which may be caused in forming parts on account of technical parameters, equipment performance, material characteristics, and other factors in the process of metal powder laser rapid forming. The results show that less or over accumulation resulting from powder feed delay is the main reason for affecting the dimensional accuracy of cladding and the main reason which affects the appearance of surface sticky powder is specific energy.…”
Section: Introductionmentioning
confidence: 99%
“…Titanium alloy plate is a kind of alloy product with following advantages: (1) Strong but pliable in texture, favorable in shape, and can be made into appropriate radian conformable to chest walls so as to protect the normal volume and respiratory function of chest to a lager extent without inducing rejection responses in human body (Shang et al, 2011); (2) Simple in operation and can be covered on defect surfaces of chest walls by threading several stitches with steel wires; (3) Larger in intensity so as to confront with outside violence and protect intrathoracic organs; (4) No subcutaneous drainage is required as the subcutaneous effusion can flow into fchest through holes of titanium alloy plates and been discharged through thoracic ducts (Thomas et al, 2010). Berthet et al found in their study that a female patient with non-small cell lung cancer (NSCLC) was performed with upper right lobectomy and mediastinal lymph node dissection synchronizing with the resections of 3rd, 4th, 5th and 6th ribs and corresponding vertebrae on right rear side followed by reconstruction of the defect chest walls with rib osteosynthesis of vertical peptide and polytetrafluoroethylene mesh, after which no complication like thorax deformation, displacement, respiratory depression and infection was observed during follow-up .…”
Section: Value Of Porous Titanium Alloy Plates For Chest Wall Reconstmentioning
confidence: 99%